2020
DOI: 10.23939/jtbp2020.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris in wastewater treatment processes – practical experience

Abstract: Wastewater from human settlements contains a significant amount of organic and biogenic substances. Insufficiently treated wastewater enters surface water and leads to their eutrophication. The usage of microalgae in wastewater treatment has significant advantages in comparison with other methods of removing biogenic substances. Namely: effective and simultaneous removal of nitrogen and phosphorus without reagents management facilities, oxygen formation. Using microalgae in wastewater treatment is a new enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…According to that table, TSS increased in both treatments. In field applications, Vovk et al (2020) [22] used C. vulgaris in a WWTP system in Ukraine. The results showed TSS removal efficiencies of 93.57-96.84% at 14 and 30 days after microalgae inoculation.…”
Section: Changes In Wastewater Characteristicsmentioning
confidence: 99%
“…According to that table, TSS increased in both treatments. In field applications, Vovk et al (2020) [22] used C. vulgaris in a WWTP system in Ukraine. The results showed TSS removal efficiencies of 93.57-96.84% at 14 and 30 days after microalgae inoculation.…”
Section: Changes In Wastewater Characteristicsmentioning
confidence: 99%
“…Analysis of selected parameters was carried out in various studies utilizing Chlorella vulgaris, and results revealed a high removal percentage efficiency for every WWT quality 2016) observed an 88%, 82%, and 54% reduction in BOD, N, and P, respectively. Experimental research of Chlorella vulgaris usage in WWT processes was also performed by Vovk et al (2020), wherein the effect of treatment varied for BOD (95.67%), COD (83.73%), ammonium nitrogen concentration (95.93%), phosphates (96.92%), and suspended solids (96.84%) reduction efficiency within the 10.5° to 20°C temperature range of wastewater. Lastly, an analysis of all selected parameters carried out by Ahmad et al, (2014) results in a maximum reduction percentage of almost 100%; for BOD (100%), COD (99.9%), NO3…”
Section: Industrial Originsmentioning
confidence: 99%